2021
DOI: 10.1016/j.ocecoaman.2021.105576
|View full text |Cite
|
Sign up to set email alerts
|

Beachgoer perceptions on health regulations of COVID-19 in two popular beaches on the Brazilian Amazon

Abstract: The sandy beaches of the Brazilian Amazon coast have enormous touristic potential and attract thousands of visitors each year, principally in July, at the beginning of the summer vacation period. In 2020, beach going was affected worldwide by the Covid-19 pandemic, but how did the pandemic affect recreational beach use on the Amazon coast in the Brazilian state of Pará? Given this, the objective of this work is to identify public perception in compliance with health safety established by authorities due to COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…For the first occasion in modern times, most of the coastline studied has developed features of marine protected areas. Recent reports from the southeast coast of India (Prakash et al, 2021) and in Brazil (Pereira et al, 2021) contain similar findings to those here.…”
Section: Discussionsupporting
confidence: 92%
“…For the first occasion in modern times, most of the coastline studied has developed features of marine protected areas. Recent reports from the southeast coast of India (Prakash et al, 2021) and in Brazil (Pereira et al, 2021) contain similar findings to those here.…”
Section: Discussionsupporting
confidence: 92%
“… Zielinski and Botero (2020) concluded that besides the cultural factors, tourists may underestimate the risk of tourism after the pandemic due to voluntary nature to taking the risk, optimistic bias, social amplification effect, lack of reliable information, and lack of relevant experience. Pereira et al (2021) identified beach tourists’ perception on health regulations of the COVID-19 in two beaches on Brazilian Amazon. Carvache-Franco et al (2021) analyzed the tourism labels on Twitter about coastal tourism and marine tourism during the pandemic, and pointed out that “escape” and “sunshine and beach” were the main travel motivations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These findings can be used to formulate recommendations for managers of municipal beaches. By introducing sanitary measures, recreational facilities could improve public perceptions of safety, attract more visitors and aid financial recovery from the pandemic (Milanes et al, 2021;Pereira et al, 2021).…”
Section: Analysis Of Questionnairesmentioning
confidence: 99%